2022
DOI: 10.47108/jidhealth.vol5.iss4.258
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum blues reviewed by the risk factors in Indonesia

Abstract: Background: Postpartum blues are known as postpartum sadness that could initiate a more serious mental disorder. It causes a decrease in the mother's interest in her baby, failure to breastfeed, to acts of hurting the baby and themself. Knowing the determinant factors of postpartum blues as a prevention effort is necessary. Therefore, this review aims to assess the factors contributing to postpartum blues, especially in Indonesian mothers.  Methods: A review of all peer-reviewed journal-published studies on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Data reported by Vaezi et al (2019) who found no relationship between postpartum depression and education. This is inversely proportional to the research of Nurhayati & Sophia (2022), during the Covid-19 period the causes of postpartum blues were education, age, and economy (Utami & Nurfita, 2022).…”
Section: Causes Of Postpartum Bluesmentioning
confidence: 96%
See 1 more Smart Citation
“…Data reported by Vaezi et al (2019) who found no relationship between postpartum depression and education. This is inversely proportional to the research of Nurhayati & Sophia (2022), during the Covid-19 period the causes of postpartum blues were education, age, and economy (Utami & Nurfita, 2022).…”
Section: Causes Of Postpartum Bluesmentioning
confidence: 96%
“…Postpartum blues is caused by husband's support (Renata & Agus, 2021;Utami & Nurfita, 2022), high levels of stress, parity (Handayani et al, 2021), abuse, depression during pregnancy, and marital dissatisfaction (Ghosh & Bhat, 2022), premature birth (Okunola et al, 2021) are also causes of postpartum blues (Hutchens & Kearney, 2020). According to Purwati & Noviyana (2020), concern for babies, tired mothers, comments from people around them about mothers, support and presence of husbands (Handayani et al, 2021), adaptation to the presence of babies are factors that can cause postpartum blues (Purwati & Noviyana, 2020).…”
Section: Causes Of Postpartum Bluesmentioning
confidence: 99%